Peningkatan Kesadaran dan Pemberdayaan Masyarakat Pesisir Terhadap Lingkungan di Desa Persiapan Empol, Kecamatan Sekotong, Kabupaten Lombok Barat - Merta, I Wayan; Ilmi, Muhamad Yazid Mizanul; Jamí’’yyah, Shafro’Khuluq; Putri, Hermaya Sura; Aini, Jannatul; Delphi, Syakila Gita; Utami, Ulya Febria; Ropidah, Risky Riyyatul; Niarni, Baiq Gina Amalia; M.Alhafizin; Astuti, Julya (Universitas Mataram, 2025)
The waste problem along the coast of Persiapan Empol Village poses a serious threat to the environment and community welfare, primarily due to household, market, and daily waste that is often carelessly disposed of into the river. In response, the Thematic Community Service Team from Universitas Mataram implemented a program to raise community awareness about waste management and empower them to transform waste into environmentally and economically beneficial products. This activity aims to increase public awareness of environmental issues, particularly waste management. The methods used include socialization, practical training, and community empowerment, focusing on enhancing community participation. As a result, residents are now more aware of the importance of waste management, and the village administration has provided land for a temporary disposal site (TPS) and urged residents not to dispose of waste in the river. This program demonstrates positive progress in efforts to preserve the coastal environment.